The Impact Of The Covid-19 Pandemic On Interest In Entrepreneurs Based On Digital Business In MSME - Moh Yasir; Heri Pratikto; Puji Handayati (Profesional Muda Cendekia Publishing, 2021)
At the beginning of 2020, there was a global attack that caused almost the whole world including Indonesia to be shocked by the virus, namely Covid-19. The impact of the Covid-19 pandemic has caused the Indonesian economy to weaken, many entrepreneurs suffered massive losses due to the Covid-19 pandemic. One of the MSMEs affected is MSME processing apples in Bumiaji Village, Batu City, with the Covid-19 pandemic, MSME processingapples are trying to adapt to the situation by utilizing digital-based businesses. The methodological approach used in this research is a qualitative method using case studies. Data were collected using in-depth interviews by going through the process of data collection, data reduction, data presentation and conclusions. The data analysis technique was the researcher's data analysis technique using the Semiotic data analysis technique. The subject of this research is the head of MSMEs and several other MSMEs. This study found that MSMEs processingapples in Bumiaji Village suffered huge losses and there was one MSME that went out of business because their capital was forfeited. However, with the Covid-19 pandemic, MSMEs processingApples in Bumiaji Village did not stay silent, but MSMEs in Bumiaji Village made changes to their sales strategy by utilizing online business using digital businesses that they understood. With the experience they learn about digital-based business. Even though MSME owners have weaknesses in human resources which result in them not being able to maximize their sales strategy. With these limitations, MSME owners have a high interest in doing digital-based business.